2005
DOI: 10.1007/s11249-004-1759-6
|View full text |Cite
|
Sign up to set email alerts
|

Tribological performance of three advanced piston rings in the presence of MoDTC-modified GF-3 oils

Abstract: The piston assembly (piston ring and cylinder bore) is one of the key parts of the internal combustion (IC) engine. Its performance will directly determine the performance of the whole engine. The piston assembly's tribological performance will be influenced by both its mechanical properties and the tribochemical interactions that take place on their surfaces. In this paper, three kinds of advanced stainless steel piston rings with a single nitrided layer, CrN coating on the nitrided layer and a B 4 C and CrN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 16 publications
1
11
0
2
Order By: Relevance
“…Like ZDDP, MoDTC is relatively indifferent to the nature of the substrate on which it forms MoS 2 . Thus, it reduces friction not just on steel but also on pre-formed ZDDP tribofilms [56], ceramics [57] and DLCs [58]. Graham et al found that the formation of MoS 2 from MoDTC and consequent friction reduction was strongly dependent on the severity of the contact conditions [59].…”
Section: Discussionmentioning
confidence: 99%
“…Like ZDDP, MoDTC is relatively indifferent to the nature of the substrate on which it forms MoS 2 . Thus, it reduces friction not just on steel but also on pre-formed ZDDP tribofilms [56], ceramics [57] and DLCs [58]. Graham et al found that the formation of MoS 2 from MoDTC and consequent friction reduction was strongly dependent on the severity of the contact conditions [59].…”
Section: Discussionmentioning
confidence: 99%
“…The friction and wear properties of each disc specimen were investigated using a reciprocating Optimol SRV tribometer [12,14,15] against ASTM 52100 steel balls with a diameter of 10.0 mm and polytetrafluoroethylene (PTFE) balls with a diameter of 9.5 mm. These friction tests were performed under lubrication using a typical oil used in the sliding guide-ways of machine tools.…”
Section: Methodsmentioning
confidence: 99%
“…Oil is an important class of liquid lubricant while grease falls in the category of semi-solid ones. The lubricating characteristic of oil lubricants is very much controlled by the nature of the base oil and the additives therein (Ref [4][5][6]. Solid lubricants are among the important constituents of additives .…”
Section: Introductionmentioning
confidence: 99%